DESAIN SARANA BAWA PERALATAN OLAHRAGA ANGGAR UNTUK KEPERLUAN LATIHAN RUTIN - Vincentius, Royke; H, Ilosa Dwi (JURNAL KREATIF: DESAIN PRODUK INDUSTRI DAN ARSITEKTUR, 2018)
AbstractFencing is a martial arts using weapons that had been develoed into an agility sport with weapons that emphasize on ability techniques such as cutting, stabbing or fending off opponent's weapons by using the skill in utilizing hand agility. In order to gain high skill the athletes must do routine exercises. For the purpose the athletes need some carrying device that is design accordingly. The research conduct in order to design specific carrying device for this specific purposes. The design method begin with data collecting, analysing the data, determine the design concept, create alternative design, develop alternative design, until the final design. A special carrying device for placing the fencing equipment is then designed for specific purpose that is for routine exercise. Equipped with a regular and neat configuration, and prioritizes comfort and security for users the carrying device is design adopting the Vintage style, for a more luxurious, elegant, yet traditional.Keywords: fencing, evintage, fencing equipment, carrying tool.